Isolation of molybdenum(vi) from simulated leachates of irradiated uranium-aluminum targets using diluted and undiluted sulfate ionic liquids. Issue 14 (3rd July 2019) - Raiguel, Stijn; Dehaen, Wim; Binnemans, Koen
Abstract : A method is presented to separate molybdenum from other elements commonly present in oxidative alkaline leachates of irradiated uranium-aluminum targets for the production of molybdenum-99. Abstract : A method is presented to separate molybdenum from other elements commonly present in oxidative alkaline leachates of irradiated uranium-aluminum targets for the production of molybdenum-99. The separation was accomplished by selective extraction of molybdate anions using triazolium and phosphonium sulfate ionic liquid extractants, either diluted in 1-octanol or undiluted. Molybdenum was then stripped from the organic phase using a sodium hydrogen carbonate solution. The extractant was regenerated by contacting the organic phase with an alkaline sulfate solution. The extraction mechanism and the influence of the diluent on the extractant performance were investigated. The reported method provides a promising alternative to state-of-the-art chromatographic processes, showing potential for limiting the production of radioactive waste.